1991
DOI: 10.1038/hdy.1991.52
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of Gammarus fossarum populations

Abstract: The population structure of Gammarus fossarum Koch was analysed at six enzyme loci in 38 populations from the Danube and Rhine drainage system in the southern part of Germany. The species-restricted distribution to the upper reaches of rivers was reflected in the large genetic differentiation of all populations. The genetic pattern can be explained as a dynamic balance between genetic drift and restricted gene flow. As migration mainly occurs along the rivers, a treelike pattern showing the genetic relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…The apparent lack of gene flow among most of gammarid populations may reflect their degree of geographic isolation. This was previously observed through allozyme studies for populations of G. fossarum from the Danube and Rhine drainage systems (Siegismund and Mü ller, 1991) and is also true for the closely spaced populations of G. fossarum in the Grenoble region, for which mtDNA polymorphism is further investigated elsewhere (Meyran and Taberlet, 1996a).…”
Section: Intraspecific Differentiationmentioning
confidence: 57%
See 2 more Smart Citations
“…The apparent lack of gene flow among most of gammarid populations may reflect their degree of geographic isolation. This was previously observed through allozyme studies for populations of G. fossarum from the Danube and Rhine drainage systems (Siegismund and Mü ller, 1991) and is also true for the closely spaced populations of G. fossarum in the Grenoble region, for which mtDNA polymorphism is further investigated elsewhere (Meyran and Taberlet, 1996a).…”
Section: Intraspecific Differentiationmentioning
confidence: 57%
“…Geographic variation among local populations also occurs genetically, as previously observed for some species after isozyme analysis (reviewed in Siegismund and Mü ller, 1991). However, data on interregional intraspecific variation using such classical discriminating tools have encouraged the recognition of subspecies or sibling species, which may be a source of taxonomic confusion between ''classical species'' and ''deviating forms'' (Scheepmaker, 1990).…”
Section: Intraspecific Differentiationmentioning
confidence: 93%
See 1 more Smart Citation
“…fish, [10], [11]), and intermediate hosts for parasites [12]. Multiple studies have shown high levels of population differentiation [13] as well as the evolution of reproductively isolated cryptic species [14][16] within morphological species. The fact that such pronounced genetic structure arises despite frequently observed large population sizes with hundreds to thousands of individuals per m 2 [17][19] suggests substantial limitations of gene flow between populations.…”
Section: Introductionmentioning
confidence: 99%
“…Several population genetic studies have been conducted on G. fossarum , but often focused on limited geographical regions containing only one of the cryptic species and/or were constrained by the limited availability of highly variable and selectively neutral markers [13], [14], [35], [38][40]. We here make use of nine recently developed microsatellite markers [41] to examine the intraspecific genetic structure within two cryptic species and potential differences between them.…”
Section: Introductionmentioning
confidence: 99%